DETERMINANTS OF LABOR ALLOCATION IN LONTAR FARMING IN OETUTULU VILLAGE, NORTHWEST ROTE DISTRICT, ROTE NDAO REGENCY - Sinar, Maria Eresta; Suek, Johanna; Bani, Aplonia; Hendrik, Ernantje (Buletin Ilmiah Impas, 2025)
Lontar palm is a leading commodity in Rote Ndao Regency, particularly for rural communities that depend on its products, such as palm sugar, palm wine, and handicrafts. However, lontar farming is still carried out traditionally and faces various constraints, including limited equipment, labor availability, and market access that remains suboptimal. The basic method used in this study was descriptive quantitative research. This study aimed to identify the profile of lontar farming, describe the profile of lontar farming, and estimate the determinants of labor allocation in lontar farming. Respondents were selected randomly using a simple random sampling method, involving 55 lontar tappers. The analytical techniques used were man-days (HOK) analysis and multiple linear regression analysis. The results showed that the average labor allocation of lontar farmers was 28.6 man-days per season, with tapping being the activity that absorbed the greatest amount of labor. Based on the multiple linear regression analysis of the seven variables examined, namely age, education, number of family members, labor, farming experience, number of trees, and number of inflorescence clusters per tree, only the number of trees had a significant effect on labor allocation. This means that the more trees tapped by farmers, the greater the labor required.